Taxation of Islamic Banking Products under the Nigerian Laws Issues, Problems and Prospects - Muhammed, Olokooba Saka (2014)
After almost four decades of the revival of Islamic banking globally, and over twenty one years of promulgating Banks and Other Financial Institutions Decree (BOFID), a law that prepared legal ground for the operation of Islamic banking in Nigeria, the current three major laws that regulate Banking activities and Company’s taxation in Nigeria-the Banks and Other Financial Institutions Act, the CBN Acts and the Companies Income Tax Act are yet to provide adequate guideline for the taxability of Islamic Finance. This is a lacuna in both the administration as well as the taxation of Islamic banking activities in Nigeria. This paper therefore addresses the issue of the taxability of Islamic banking products and the likely problems thereto under the Nigerian Law. Apart from other general solutions proffered, the paper ends with a recommendation that a model law and clear regulations on Non-Interest Finance be urgently put in place to take care of the tax aspect of Islamic Finance in Nigeria.
Keywords: Islamic Banking; Nigerian Laws; Problems; Prospects; Taxation